Profits for Economists - Thomas Karier (Levy Economics Institute of Bard College, 1993)
There is no single best estimate of profits because different purposes require measures. For example, profits in national income should be different than profits in financial statements. But given these differences, there are certain economic standards that should apply to all profit measures. These standards are described and then used to evaluate the appropriateness of several currently available measures of profits including those reported by the National Income and Product Accounts, Internal Revenue Service, Quarterly Financial Report, Compustat, and Business Week.
Keywords: 330